2017
DOI: 10.2337/db16-1009
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Protects Pancreatic β-Cells From Death by Increasing Autophagic Flux and Restoring Lysosomal Function

Abstract: Studies in animal models of type 2 diabetes have shown that glucagon-like peptide 1 (GLP-1) receptor agonists prevent β-cell loss. Whether GLP-1 mediates β-cell survival via the key lysosomal-mediated process of autophagy is unknown. In this study, we report that treatment of INS-1E β-cells and primary islets with glucolipotoxicity (0.5 mmol/L palmitate and 25 mmol/L glucose) increases LC3 II, a marker of autophagy. Further analysis indicates a blockage in autophagic flux associated with lysosomal dysfunction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 48 publications
(71 reference statements)
8
118
1
Order By: Relevance
“…4B). The results confirm previous findings that ER stress contributes to Oleate enhances ␤-cell autophagy the stimulation of autophagic flux due to palmitate (20,25), but now show that this mechanism does not account for the response due to oleate.…”
Section: Er Stress Mediates Autophagy In Response To Palmitate But Nosupporting
confidence: 89%
See 3 more Smart Citations
“…4B). The results confirm previous findings that ER stress contributes to Oleate enhances ␤-cell autophagy the stimulation of autophagic flux due to palmitate (20,25), but now show that this mechanism does not account for the response due to oleate.…”
Section: Er Stress Mediates Autophagy In Response To Palmitate But Nosupporting
confidence: 89%
“…One interpretation of this variability is that palmitate exerts multiple and conflicting effects on autophagy, the balance of which determines the overall outcome. One positive input is almost certainly ER stress (20,25). Thus we found that PBA inhibited autophagic flux in the presence of palmitate, reducing LC3II to levels below those of CQ alone (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Hyperlipidaemia was induced by 500 μmol/L OA, 500 μmol/L PA or 250 μmol/L oleic acid +250 μmol/L palmitic acid (OA+PA), as used by others. 22,31 This was the maximal dose which did not significantly reduce cell number or induce apoptosis ( Figure S3A…”
Section: Hyperglycaemia Increases Ld and Plin2 In Ins-1mentioning
confidence: 99%